2020
DOI: 10.21608/jfds.2020.95596
|View full text |Cite
|
Sign up to set email alerts
|

Production of Probiotic Low-Fat Yoghurt Supplemented with Guava Seeds Powder

Abstract: Guava seeds powder (GSP) is rich source of crude fiber, minerals, and antioxidants compounds. The present study was administered to evaluate the effect of supplementation with GSP on the physicochemical, rheological, and sensory properties of probiotic low-fat yoghurt. GSP was added at ratios of 1, 2, and 3%. A gradual increase in crude fiber, Acidity, viscosity, total phenolic content, and antioxidant activity was recorded in GSP-enriched yoghurt as the GSP ratio increased. On the other hand, the pH values an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Abd El -Sattar et al, (2020) found that the Total Phenolic Content (TPC) and Radical Scavenging Activity (RSA) of yoghurt prepared with guava seeds powder was increased as guava seeds powder % increase in yoghourt product. The authors concluded that guava seeds powder could be used as natural additives to improve physicochemical, rheological and sensory properties of low fat youghurt.…”
Section: Discussionmentioning
confidence: 99%
“…Abd El -Sattar et al, (2020) found that the Total Phenolic Content (TPC) and Radical Scavenging Activity (RSA) of yoghurt prepared with guava seeds powder was increased as guava seeds powder % increase in yoghourt product. The authors concluded that guava seeds powder could be used as natural additives to improve physicochemical, rheological and sensory properties of low fat youghurt.…”
Section: Discussionmentioning
confidence: 99%